Novel enzyme‐based electrochemical and colorimetric biosensors for tetracycline monitoring in milk. (26th January 2021) - Besharati, Maryam; Tabrizi, Mahmoud Amouzadeh; Molaabasi, Fatemeh; Saber, Reza; Shamsipur, Mojtaba; Hamedi, Javad; Hosseinkhani, Saman
Abstract: Recently, there has been a growing demand to develop portable devices for the fast detection of contaminants in food safety, healthcare, and environmental fields. Herein, two biosensing methods were designed by the use of nicotinamide adenine dinucleotide phosphate (NAD(P)H)‐dependent TetX2 enzyme activity and thionine as an excellent electrochemical and colorimetric mediator/probe to monitor tetracycline (TC) in milk. The nanoporous glassy carbon electrode (NPGCE) modified with polythionine was first prepared by electrochemically and then TetX2 was immobilized onto the NPGCE using polyethyleneimine. The prepared biosensor provided a high electrocatalytic response toward NAD(P)H by significantly reducing its overpotential. The proposed biosensor exhibited a detection limit of 40 nM with a linear range of 0.1–0.8 μM for TC determination. Besides, the thionine probe was used to develop a novel colorimetric assay using a simple enzymatic color reaction within a few minutes. The limit of detection for TC was experimentally achieved as 60 nM, which was lower than the safety levels established by the World Health Organization (225 nM). The correlation between change in the color of the solution and the concentration of TC was used for quality control of milk samples, as confirmed by the standard high‐performance liquid chromatography method. The results show the great potential of the proposed assays as portable instruments for on‐site TC measurements. Abstract : xxxxxx